History Taking and Assessment - Forlenza, Orestes V.; Pereira, Marta L.G.F.; Canineu, Paulo R.; Stella, Florindo [UNESP] (My University, 2019)
The clinical history is a fundamental part of the medical semiology. It requires assessing the patient with a holistic approach and demands special attention to specific elements that may allow a deeper understanding of disease process and its progression over time. In the present text, we emphasize some of the most relevant aspects of history taking in geriatric psychiatry, including the characterization of premorbid features, personal and family history, and the establishment of an accurate estimate of cognitive/functional status and behavioral symptoms both in primary (functional) and secondary (organic) psychiatric disorders. The identification of risk factors for neuropsychiatric disorders associated to general medical conditions is another important element, for the modification of these factors (whenever possible) may be crucial for overall response and prognosis. We further propose that use of psychometric scales in clinical practice not only yields the objective measurement of baseline cognitive/functional state for diagnostic purposes but also enables the clinician to monitor changes during follow-up, particularly those related to treatment response.
Keywords: Assessment; Cognition; Diagnosis; Geriatric psychiatry; Psychopathology